Existence and uniqueness of solution for a fractional Riemann-Liouville initial value problem on time scales - Benkhettou, Nadia (2016)
We introduce the concept of fractional derivative of Riemann-Liouville on time scales. Fundamental properties of the new operator are proved, as well as an existence and uniqueness result for a fractional initial value problem on an arbitrary time scale. © 2015 The Authors.